Peran Partisipasi Masyarakat Dalam Mewujudkan Good Governance Di Era Digital - Sri Yulianti Mozin; Vivi Venti Vera Sulila; Adityan N. Yusuf (Jurnal Politik dan Pemerintahan Daerah, 2025)
This study, entitled "Public Participation Messages in Achieving Good Governance in the Digital Era," aims to analyze how public participation through digital media can improve the quality of good governance in Indonesia. The background to this research is based on the rapid development of information technology, which has encouraged the formation of new participatory spaces between the public and the government. Research data shows a significant increase in public digital participation, from 40% in 2015 to 85% in 2023, with a projection of 90% by 2025. This coincides with an increase in the good governance index from 50% to 85% during the same period (BPS, 2023; Ministry of Communication and Information, 2024). The method used in this study is a qualitative descriptive approach with secondary data analysis techniques from various official sources such as We Are Social, BPS, and the Ministry of Communication and Information. The theory used refers to Dwiyanto's (2020) perspective on the principles of participation, accountability, and transparency in governance, as well as the opinions of Sukamto (2021) and Rahman & Yuliana (2022) regarding the importance of digital participation as an effective means of public communication. The research results show a positive correlation between increased public digital participation and improvements in the good governance index. Digital media is an effective means for the public to express their aspirations, monitor public policies, and strengthen government transparency and accountability. However, this study also identified challenges in the form of a digital divide and low digital literacy in rural areas (Hidayat, 2023). In conclusion, public participation in the digital era plays a strategic role in realizing good governance. Inclusive policies and equitable access to technology are needed so that all levels of society can actively contribute to the development process, oversight, and transparent and accountable public decision-making.